1975
DOI: 10.1021/jo00899a049
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide chemistry. Convenient synthesis of dialkyl peroxides

Abstract: Using a mortar and pestle and working in a glove bag under an atmosphere of dry nitrogen, lumps of potassium superoxide, purchased from K & K Chemicals, were ground to a fine consistency before use. (9) G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…KO 2 , a commonly used carrier, has low solubility in DMSO (Merritt and Sawyer 1970, Sawyer et al 1983, Moorcroft et al 2003. Whereas crown ethers can be used to improve the solubility of KO 2 (Johnson and Nidy 1975, Valentine and Curtis 1975, Sawyer et al 1983, the more soluble quaternary ammonium superoxide Foote 1976, Sawyer et al 1983) is an alternative. In addition, the use of quaternary ammonium salts Brought to you by | University of California Authenticated Download Date | 1/5/15 6:04 AM is reported to increase not only the stability of the electrogenerated superoxide anion but also its nucleophilicity (Merritt andSawyer 1970, Moorcroft et al 2003).…”
Section: Pyrrmentioning
confidence: 99%
“…KO 2 , a commonly used carrier, has low solubility in DMSO (Merritt and Sawyer 1970, Sawyer et al 1983, Moorcroft et al 2003. Whereas crown ethers can be used to improve the solubility of KO 2 (Johnson and Nidy 1975, Valentine and Curtis 1975, Sawyer et al 1983, the more soluble quaternary ammonium superoxide Foote 1976, Sawyer et al 1983) is an alternative. In addition, the use of quaternary ammonium salts Brought to you by | University of California Authenticated Download Date | 1/5/15 6:04 AM is reported to increase not only the stability of the electrogenerated superoxide anion but also its nucleophilicity (Merritt andSawyer 1970, Moorcroft et al 2003).…”
Section: Pyrrmentioning
confidence: 99%
“…HzO Zn(0,) + PtO -Pt(02) + ZnO Likewise, a similar process may occur between the electrode surface and the H202 that is produced via reactions 2 and 7 P t O + Hz02 -Pt(O2) + H2O (16) In the case of Mn(I1) ions, the presence of H202 from the proton induced disproportionation of 02-(reactions 2 or 7) can lead to the production of .OH radicals Mn" + H202 -Mn111(OH)2+ + .OH (17) *OH Pt + .OH -Pt(OH)* -PtO + H2O (18) Because the weakest solvation of 02-occurs in MeCN (of the solvents that have been considered in the present study), superoxide should exhibit its maximum reactivity in this solvent. The peak separations for the 02/02-cyclic voltammograms with metal electrodes strongly support this proposition ( Figure 5 and Table I).…”
Section: (15)mentioning
confidence: 99%
“…Attempted mation of alkyl and acyl peroxides and hydro-isolation of 2 from solution led inevitably to peroxides using free superoxide with a1ky1 and violent explo.yions. The identity of 2 was inferred acyl halides, and sulphonate esters have been reported (4)(5)(6). It was further shown that super-X oxide is a moderately active nucleophile in displacement reactions of alkyl and electrophilic aryl halides (6-9).…”
Section: During the Past Decade There Has Been Goodmentioning
confidence: 99%
“…3b was purified by preparative tlc (benzene as eluant); nmr (CDCI,) 6 4.62 (2H, s), 4 Hydrolysis of 3a, b, c 3a, b, c (2 mmol) were dissolved in 10 ml EtOH 95%. Concentrated H2S04 (1 ml) was added and the mixture was refluxed for 1 h. The cooled solution was neutralized carefully with aqueous NaOH (2073, saturated with NaCI, and extracted with ether.…”
Section: O-lodomethylbenzenemethyl I-phthalanyl Ether 3bmentioning
confidence: 99%